Wedelia figueiredoana (Asteraceae, Heliantheae), a winged cypselae new species of Wedelia for Brazil - Bueno, Vinicius R.; Rodrigues, Leonardo S.; Sousa, Francisco Diego; Souza, Izaías C. [UNESP]; Marzinek, Juliana; Marques, Danilo (Pensoft Publishers, 2024)
We describe one new species from Ceará state, Brazil: Wedelia figueiredoana. It is morphologically associated with W. bonplandiana, but distinguished by 0.25–1.05 cm leaf blade width (vs. 1.5–2.6 cm), linear to narrow oblong leaf blade (vs. elliptic to spatulate), 3-seriate involucre (vs. 2-seriate), and cypselae 3.9–4 mm long (vs. 6–7 mm). An anatomical analysis of cypselae is provided, and we propose a more accurate terminology to describe similar wings to Wedelia species. We also provide a scientific illustration of the new species, photos of habitat, a map of its geographic occurrence, and its taxonomic affinities are discussed with a taxonomic key to the Wedelia species with the apically pronounced wings in the cypselae.
Keywords: Auricular projections; Cerrado; Compositae; fruit anatomy